How do higher education policies influence the shaping of sustainable development values in China: a three-dimensional framework - Wei, Changwei; Chen, Jiali (Frontiers in Environmental Science, 2024)
IntroductionIn the face of global challenges, higher education is regarded as an important force to promote the achievement of the 2030 Sustainable Development Goals (SDGs). Existing research has focused on articulating and analyzing the impact of value shaping for sustainable growth in higher education, although articulation and systematic analysis of higher education policy remain lacking.MethodsBased on the policy tool perspective, this paper constructed a three-dimensional analysis framework by using content analysis and the PMC index model to undertake a thorough analysis of higher education policies published at the central level in China from 2009 to 2024.ResultsThis study found that current higher education policies had multiple impacts on the formation of sustainable development values: (1) In the four dimensions of sustainable development proposed by the United Nations, China's higher education policy had shown clear guiding ideology and action direction; (2) In shaping sustainable values, China's higher education policies showed clear progress in three key dimensions; (3) The value and innovation of this study in shaping the values of sustainable development in higher education policies were primarily expressed in the following aspects.DiscussionThis paper suggested a way for optimizing the design of China's higher education policies, providing empirical data and theoretical support for China's higher education policies to better promote the ideals of sustainable development.